Oxadiazole-Based Highly Efficient Bipolar Fluorescent Emitters for Organic Light-Emitting Diodes - Wu, Qiong (Molecules, 2018)
In this study, a series of bipolar fluorescence emitters named 2DPAc-OXD, DPAc-OXD, 2PTZ-OXD and PTZ-OXD were designed and synthesized with excellent yields. The characterization of materials was investigated by using nuclear magnetic resonance (NMR) ((1)H, (13)C), mass spectrometry and thermogravimetric analysis (TGA). To investigate device efficiencies, two different OLED devices (Device 1, Device 2) were fabricated with two different host materials (Bepp(2), DPEPO). The Device 2 with 2PTZ-OXD as fluorescent emitter exhibited excellent power and current efficiencies of 6.88 Lm/W and 10.10 cd/A, respectively. The external quantum efficiency of 2PTZ-OXD was around 3.99% for Device 2. The overall device properties of phenothiazine donor were better than acridine derivatives.